1974. International Avant-Garde Art at the Palais des Beaux-Arts - D'hooghe, Joris; Herbert Foundation, Gent; Hanssens, Laura (Ghent : Herbert Foundation, 2018)
Andre, Carl ; Broodthaers, Marcel ; Buren, Daniel ; Burgin, Victor ; Gilbert & George ; Kawara, On ; Long, Richard ; Richter, Gerhard
In line with the event 1974. International Avant-Garde Art at the Palais des Beaux-Arts which took place in the Archive room of Herbert Foundation on Sunday 3 June 2018, this publication discloses the research on the exhibition Carl Andre / Marcel Broodthaers / Daniel Buren / Victor Burgin / Gilbert & George / On Kawara / Richard Long / Gerhard Richter, organised at the initiative of Yves Gevaert in 1974 at the Palais des Beaux-Arts in Brussels. With this publication, Herbert Foundation wishes to highlight the unique and international nature of the exhibition and underline its historical significance.(from Herbert Foundation)
Joris D'hooghe in conversation with Daniel Buren, Herbert Foundation, Ghent, 3 june 2018
boek